To the problem of canonical factorization for Markov additive processes - Bratiichuk, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We extend the well-known results on canonical factorization for Markov additive processes with a finite Markov chain to the case where this chain is countable. We also formulate some corollaries of these results.